ANALISIS FAKTOR YANG MEMPENGARUHI KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI WILAYAH KERJA PUSKESMAS LONDUT KABUPATEN LABUHAN BATU UTARA TAHUN 2021 - Ade Aulia Siahaan (Jurnal Kajian Kesehatan Masyarakat, 2022)
Dengue Hemorrhagic Fever (DHF) is still a public health problem in Indonesia, one of the endemic diseases with morbidity rates that tend to increase and even often causes Extraordinary Events (KLB) which are influenced by several factors, namely the host (human), agent (mosquito) and the environment. (environmental geographical conditions and demographic conditions). The purpose of this study was to analyze the factors that influence the incidence of Dengue Hemorrhagic Fever (DHF) in the Londut Health Center Work Area, Labuhan Batu Utara Regency in 2021.This type of research is an observational study with a case control study design with the number of case groups as many as 45 people and the control group as many as 45 people. The analysis used in this research is univariate, then bivariate test using Chi Square test and multivariate test using multiple logistic regression test.The results showed that there was a significant effect between Knowledge (P value 0.06 , OR: 3.692 and 95% CI: 1.534 – 8.886), Action (P value 0.011 , OR: 3.321 and 95% CI: 1.394 – 7.915), Temperature ( P value 0.003, OR: 4.054 and 95% CI: 1.678 – 9.798), lighting (P value 0.011, OR: 3.294 and 95% CI: 1.388 – 7.819) and respondent knowledge is the most dominant variable on the incidence of Dengue Hemorrhagic Fever (DHF). ) in the working area of the Londut Health Center, Labuhan Batu Utara Regency. It is recommended for the community to maintain a clean and healthy lifestyle and participate in efforts to eradicate dengue hemorrhagic fever (PSN-DHF) and health workers to increase regular counseling to the community about increasing public knowledge about dengue and the importance of adequate lighting in home.